The Challenge of Greening Religious Schools by Improving the Environmental Competencies of Teachers - Robina-Ramírez, Rafael; Sánchez-Hernández, M. Isabel; Jiménez-Naranjo, Héctor V.; Díaz-Caro, Carlos (Frontiers in Psychology, 2020)
Even though sacred scriptures emphasise the key role that Creation and respect for living creatures play in all religions, the so-called religious schools seem to show little interest in putting this sacred mandate into effect. To shed light on this subject, this work investigates the role of teachers in the process, focusing on their environmental competencies. Our hypotheses are tested through a structural equation model on a sample of 214 biology and religion teachers from 118 Catholic schools in Spain who voluntary participated in a survey. The research findings confirm that it is crucial that environmental competencies are developed in teachers to enable the greening of schools. Theoretical and practical implications for defining the job training of teachers in religious schools are drawn from the study.